2010
DOI: 10.1177/0021998310372466
|View full text |Cite
|
Sign up to set email alerts
|

Failure Progression and Mesh Sensitivity Analyses by the Plate Element-Failure Method

Abstract: Despite the fact that fiber-reinforced composite materials have been extensively used in aerospace, defense and marine structures for many years, the high stiffness and strength properties of these materials have not yet been fully exploited. In many instances, overly rigid adherence to conservative design rules based on ‘black aluminum’ (symmetric quasi-isotropic graphite-epoxy laminates) has eroded these advantages significantly. Efforts to better understand the failure mechanisms and develop efficient and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…It was observed that the failure pattern is comparable for all plies for fiber and matrix failures. In a study conducted by Liu et al, 23 the experimental failure load at the first fiber rapture was 30,259 N, while the failure load obtained from their progressive failure analysis was 27,477.7 N, which gave 9% variation from the experimental load. Nonetheless, in our model, it was found that the failure load was 28,170 N, which indicated only a 6.9% variation compared to the experimental failure load and a 2.4% variation from those models.…”
Section: Model Validationmentioning
confidence: 94%
See 2 more Smart Citations
“…It was observed that the failure pattern is comparable for all plies for fiber and matrix failures. In a study conducted by Liu et al, 23 the experimental failure load at the first fiber rapture was 30,259 N, while the failure load obtained from their progressive failure analysis was 27,477.7 N, which gave 9% variation from the experimental load. Nonetheless, in our model, it was found that the failure load was 28,170 N, which indicated only a 6.9% variation compared to the experimental failure load and a 2.4% variation from those models.…”
Section: Model Validationmentioning
confidence: 94%
“…Further verification of the progressive failure model was carried out with a study that dealt with the progression of failure in an open-hole carbon/epoxy composite laminate with stacking sequence [45/0/ À 45/90] s subjected to tension. 23 The study used different failure theories, including the micromechanics of failure, maximum stress, Tsai-Wu, Hashin, and Puck theories with ABAQUS user subroutine, to analyze the open-hole laminate. The stress at the first load drop (first fiber rapture) was considered as the ultimate strength.…”
Section: Model Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…the Equivalent Single Layer Models (ESL): the Reissner-Mindlin (FSDT, [9,10]) and higher-order models (TSDT, [11]) have been addressed. But, only global quantities can be obtained, and the integration of the equilibrium equations is needed to estimate the transverse shear stresses with accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, many attempts have been made to investigate the progressive failure of composite laminates. The methods commonly seen in literature include the material property degradation method (MPDM), 2,3 continuum damage mechanics method (CDMM), 4–6 element failure method (EFM), 79 and so on. The MPDM assumes that the damaged material can be replaced by an equivalent one with degraded properties.…”
Section: Introductionmentioning
confidence: 99%